2009
DOI: 10.5194/bg-6-1491-2009
|View full text |Cite
|
Sign up to set email alerts
|

Methanotrophy potential versus methane supply by pore water diffusion in peatlands

Abstract: Abstract. Low affinity methanotrophic bacteria consume a significant quantity of methane in wetland soils in the vicinity of plant roots and at the oxic-anoxic interface. Estimates of the efficiency of methanotrophy in peat soils vary widely in part because of differences in approaches employed to quantify methane cycling. High resolution profiles of dissolved methane abundance measured during the summer of 2003 were used to quantity rates of upward methane flux in four peatlands situated in Wales, UK. Aerobic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 65 publications
2
55
1
2
Order By: Relevance
“…Samaritani et al (2010) showed that the strongest differences in soil respiration were observed during the warmer and drier periods. Long periods without rain may result in a sharper transition between unsaturated and saturated peat layers (Hornibrook et al 2008) and change diffusion coefficients and water saturation within the peat, which can slow down the transport of gases and solutes in the peat profile (Waddington and Roulet 1997;Fraser et al 2001;Limpens et al 2008). Our results show that the peatland carbon flux can be modified by even small changes in environmental conditions such as those induced by our treatments.…”
Section: Additive Effect Of Warming and Lowering Of Wtd On C Cyclingmentioning
confidence: 72%
“…Samaritani et al (2010) showed that the strongest differences in soil respiration were observed during the warmer and drier periods. Long periods without rain may result in a sharper transition between unsaturated and saturated peat layers (Hornibrook et al 2008) and change diffusion coefficients and water saturation within the peat, which can slow down the transport of gases and solutes in the peat profile (Waddington and Roulet 1997;Fraser et al 2001;Limpens et al 2008). Our results show that the peatland carbon flux can be modified by even small changes in environmental conditions such as those induced by our treatments.…”
Section: Additive Effect Of Warming and Lowering Of Wtd On C Cyclingmentioning
confidence: 72%
“…Recent evidence provides strong support for the occurrence of AOM in peat soils (Smemo and Yavitt, 2007), yet conclusive ev- (Smemo and Yavitt, 2006;2007), Smemo and Yavitt (2006), and Keller and Bridgham (2007). 2 values derived from Hornibrook et al (2009), Keller and Bridgham, (2007), Küsel et al (2008), and Loy et al (2004). 3 values derived from Beer and Blodau (2007), Billet and Moore (2008), Blodau et al (2007aBlodau et al ( , 2007b, and Shotyk (1997a, 1997b).…”
Section: Biogeochemistry and Electron Acceptorsmentioning
confidence: 96%
“…Methane oxidation potentials appear to be highest near the oxic/anoxic interface. Hornibrook et al (2009) found that CH 4 dissolved in the pore water of four Welsh peatland soils was nearly always zero at the groundwater table and concluded that emissions observed were predominantly mediated by vascular plants. The ability of plants with aerenchymous tissue to transport CH 4 to the atmosphere when CH 4 concentrations build up around the roots is well established (Laanbroek, 2010), and typically occurs when the soil is near saturation (Strack et al, 2006).…”
Section: S O Petersen Et Al: Annual Emissions Of Ch 4 and N 2 Omentioning
confidence: 99%
“…No attempt was made to correct CH 4 fluxes, which depend on CH 4 production in saturated parts of the soil profile, and CH 4 oxidation that may also primarily occur near the groundwater table (Hornibrook et al, 2009). At this depth diurnal temperature variations are small, i.e., any error associated with sampling time would be small.…”
Section: Effect Of Sampling Timementioning
confidence: 99%